A physically based approach for the estimation of root-zone soil moisture from surface measurements: application on the AMMA database - Manfreda, Salvatore, author; Fiorentino, Mauro, author; Samela, Caterina, author; Margiotta, Maria Rosaria, author; Brocca, Luca, author; Moramarco, Tommaso, author; Colorado State University, publisher (Colorado State University. Libraries, 2013)
In the present work, we present an application of a new formulation for the estimation of the soil moisture in the root zone based on the measured value of soil moisture at the surface. The method has been recently proposed by Manfreda et al. (2012) with the aim to provide a mathematical relationship between surface and root zone soil moisture. It derives from a simplified form of the soil water balance equation and provides a closed form of the relationship between the root zone and the surface soil moisture with a limited number of physically consistent parameters. The approach was used to interpret soil moisture dynamics at the point scale using soil moisture measurements taken from the African Monsoon Multidisciplinary Analysis (AMMA) database. These measurements form an excellent database with a significant number of measurements in time and space. Moreover, the measurements provide a detailed description of the soil moisture along the root-zone profile. According to this, we have used the surface soil moisture measurements at 5 cm depth to predict the soil moisture in the lower layer of the soil where the relative saturation is measured at various depths. The method provided good prediction of the averaged soil moisture in the root zone soil layer with the advantage that all parameters are physically consistent.
Hydrology days 2013
AGU hydrology days 2013
2013 annual AGU hydrology days was held at Colorado State University on March 25 - March 27, 2013.